The great easter egg hunt [videorecording (DVD)] - Eskenazi, Diane (Collectible classics., 2004)
Celebrate the promise of springtime in this animated adventure filled with toys, animals, music, and fun, which reminds us all to be thankful for the life we've got. Peter's grandmother sends him an Easter basket with a stuffed bunny known as Whiskers, who becomes the envy of the other toys, because he's taken to school and they stay home. After a dog snatches Whiskers from the playground, he meets some real rabbits who tell him about a magic egg that the Easter Bunny hides, which grants a wish when it is found. Peter's life is threatened by a high fever, so Whiskers and his fellow toys (Celeste, Saber, Peewee, VCR, Trog, and Harley) set out on a colorful quest to find the egg and save him.